Aktivitas Gel Ekstrak Daun Kepel terhadap Staphylococcus epidermidis FNCC 0048 dan Escherichia coli FNCC 0091 - Maulana Tegar Adityanugraha; Ferli Eko Kurniantoro; Filu Marwati Santosa Putri; Bingar Hernowo (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Infection is one of the health problems that many people experience, skin infections caused by Staphylococcus epidermidis FNCC 0048 bacteria and diarrheal diseases caused by Escherichia coli FNCC0091 bacteria. This aims of this study to determine gel concentration of antibacterial activity from ethanol extract of Kepel leaves (Stelechocarpus burahol) which shows antibacterial activity against Staphylococcus epidermidis FNCC 0048 and Escherichia coli FNCC0091. This study is an experimental study, using the well-diffusion method and the diameter of the inhibition zone. The concentrations of the Kepel leaf ethanol extract used in this study were 6%, 9%, and 12%. The analysis used is descriptive analysis. The results of the physical property tests showed that the emulgel of kepel extract had good organoleptic properties, adhesiveness, and pH. However, its spreadability did not meet the standard criteria. The results showed that the gel extract of Kepel leaves (Stelechocarpus burahol) with a concentration of 6%, 9%, and 12% was able to inhibit the growth of Staphylococcus epidermidis FNCC 0048 bacteria with an average of 2.13mm, 4.15mm, and 5.47mm respectively, while for bacteria Escherichia coli FNCC0091 with an average of 2.44mm, 3.55mm and 4.14mm respectively.The minimum concentration of ethanol extract of Kepel leaves which shows antibacterial activity against test bacteria is 3%.